Paclitaxel Plus Platinum Neoadjuvant Chemotherapy Followed by Surgery Versus Primary Surgery in Locally Advanced Cervical Cancer—A Propensity Score Matching Analysis - Zhang, Yanan; Li, Bin; Wang, Yating; Liu, Shuanghuan; Wang, Haibo (Frontiers in Oncology, 2020)
Objective: To compare the efficacy and safety of neoadjuvant chemotherapy followed by surgery (NACTS) and primary surgery (PS) in locally advanced cervical cancer (LACC). Methods：LACC (stage IB2/IIA2, FIGO 2009) patients accepted NACTS or PS in the Cancer Hospital of the Chinese Academy of Medical Sciences from 2007 to 2017 were enrolled, and a database was established. A 1:1 ratio propensity score matching (PSM) was performed for the NACTS group and PS group according to pretreatment characteristics. After PSM, the clinicopathological features and prognosis between the matched groups were compared. Results: Of 803 cases in the database, 639 met the inclusion criteria, with 428 received paclitaxel plus platinum NACTS and 211 received PS. After PSM, the two groups had comparable pretreatment characteristics, with 190 cases in each group. In the NACTS group, the operation parameters were similar to PS group except for the longer operation time (median 255min vs. 239min, P=0.007), pathological intermediate-risk factors including tumor diameter (P<0.001) and LVSI(+) (P<0.001) were significantly decreased, fewer patients were with  2 intermediate risk factors (10.5% vs. 53.2%, P<0.001) so that the rate of adjuvant radiotherapy was reduced (54.2% vs. 70.0%, P=0.002). DFS and OS were similar between the NACTS group and PS group (P0.05). However, for patients with tumor diameter 5cm or SCC 5ng/ml, DFS of the NACTS group was significantly prolonged(P=0.016, P=0.007). Conclusion: Paclitaxel plus platinum neoadjuvant chemotherapy can reduce adjuvant radiotherapy by decreasing pathological risk factors. Patients with tumor diameter 5cm or SCC 5 ng/ ml may obtain survival benefits.